2021
DOI: 10.1088/1755-1315/762/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth of Sempur (Dillenia philippinensis Rolfe) shoots in response to different types of plants growth regulators supplemented on MS medium

Abstract: Plant tissue culture of Sempur (Dillenia philippinensis Rolfe) has not been widely reported. The previous study showed that BAP added to Murashige & Skoog (MS) basal medium promoted the growth of D. philippinensis shoot culture. This research aimed to investigate the growth of D. philippinensis shoot tip cultures on MS medium containing three types of cytokinins namely BAP, Kinetin, and 2-iP compared with Gibberelic acid (GA3). The results showed that the type and concentrations of cytokinins significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Similar effects of mT on the height of micro-plantlets were reported by other researchers who studied various horticultural species (Moyo et al, 2018;Kucharska et al, 2020;Nowakowska et al, 2020). Other studies found that 2-ip might have different effects on the length of the microshoot, but for some tree crops, 2-ip can positively affect shoot growth compared to 6-BAP (Debnath;Kenneth, 2001;Faisal et al, 2006;Singh, 2020;Wulandari et al, 2021;Haida et al, 2022). The studied plant growth regulators could be arranged according to their effect on the ability to promote shoot formation in the following order: mT > 6-BAP > 2-ip.…”
Section: Shoot Multiplicationsupporting
confidence: 75%
“…Similar effects of mT on the height of micro-plantlets were reported by other researchers who studied various horticultural species (Moyo et al, 2018;Kucharska et al, 2020;Nowakowska et al, 2020). Other studies found that 2-ip might have different effects on the length of the microshoot, but for some tree crops, 2-ip can positively affect shoot growth compared to 6-BAP (Debnath;Kenneth, 2001;Faisal et al, 2006;Singh, 2020;Wulandari et al, 2021;Haida et al, 2022). The studied plant growth regulators could be arranged according to their effect on the ability to promote shoot formation in the following order: mT > 6-BAP > 2-ip.…”
Section: Shoot Multiplicationsupporting
confidence: 75%